Mechanistic Study and Regulatory Effects of Chloride Ions on the B-Z Oscillating Reaction - Lidan Niu; Lijuan Zhou; Qihui Wang; Wenjing Yang (Molecules)
This work investigated the mechanistic role of chloride ions (Cl−) in the Belousov–Zhabotinsky (B-Z) oscillating reaction. We conducted a multivariate statistical analysis of the B-Z response, established a quadratic polynomial regression model, and determined the contributions of the experimental parameters to the induction time. The results indicate that the relationship between the experimental parameters and the induction time is often nonmonotonic, exhibiting secondary dependence. Then, we studied the influence mechanism by which Cl− affects the B-Z reaction system. Both experimental and theoretical studies indicate that as the concentration of Cl− increases, the system becomes more active as the activation energy increases. When the Cl− concentration is less than 1 mmol/L, the induced apparent activation energy remains relatively constant. However, as the Cl− concentration increases from 1.00 mmol/L to 2.00 mmol/L, the induced apparent activation energy increases rapidly from 50 kJ/mol to 120 kJ/mol, which severely hinders the induction period and then increases the induction time.